2019
DOI: 10.1007/s00024-019-02394-y
|View full text |Cite
|
Sign up to set email alerts
|

The December 22, 2018 Anak Krakatau, Indonesia, Landslide and Tsunami: Preliminary Modeling Results

Abstract: On the evening of December 22, 2018, the coasts of the Sunda Strait, Indonesia, were hit by a tsunami generated by the collapse of a part of the Anak Krakatau volcano. Hundreds of people were killed, thousands were injured and displaced. This paper presents a preliminary modeling of the volcano flank collapse and the tsunami generated based on the results of a 2D depth-averaged coupled model involving a granular rheology and a Coulomb friction for the slide description and dispersive effects for the water flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
62
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 63 publications
7
62
2
Order By: Relevance
“…Heidarzadeh et al (2020a) analyzed tide gauge records of the AKT and proposed a source model for this unique tsunami by applying numerical simulations; the source model proposed by Heidarzadeh et al (2020a) consists of an initial pure-elevation wave with height of 100-150 m and length of 1.5-2.0 km. The numerical modeling of the event by Paris et al (2020) and Zengaffinen et al (2020) further reconfirmed the source model initially proposed by Heidarzadeh et al (2020a). The volume of the sliding mass during the AKT was estimated at 0.2-0.3 km 3 by Ren et al (2020) whereas Heidarzadeh et al (2020a) reported it in the range of 0.175-0.326 km 3 .…”
Section: Introductionsupporting
confidence: 65%
“…Heidarzadeh et al (2020a) analyzed tide gauge records of the AKT and proposed a source model for this unique tsunami by applying numerical simulations; the source model proposed by Heidarzadeh et al (2020a) consists of an initial pure-elevation wave with height of 100-150 m and length of 1.5-2.0 km. The numerical modeling of the event by Paris et al (2020) and Zengaffinen et al (2020) further reconfirmed the source model initially proposed by Heidarzadeh et al (2020a). The volume of the sliding mass during the AKT was estimated at 0.2-0.3 km 3 by Ren et al (2020) whereas Heidarzadeh et al (2020a) reported it in the range of 0.175-0.326 km 3 .…”
Section: Introductionsupporting
confidence: 65%
“…It has reproduced well the run-up heights of tsunamis generated by submarine landslides in application to the case of Papua New Guinea earthquake in 1998 (Imamura and Hashi 2003). Pakoksung et al (2019) analyzed the 2018 Sulawesi earthquake using this type of model. The latter granular material models include Iverson and George (2014), Ma et al (2015), Grilli et al (2019) and Paris et al (2020), whose models' landslide part governed by Coulomb friction is originated from Savage and Hutter (1989).…”
Section: Numerical Model Of Landslide Mass and Tsunamimentioning
confidence: 80%
“…Pakoksung et al (2019) analyzed the 2018 Sulawesi earthquake using this type of model. The latter granular material models include Iverson and George (2014), Ma et al (2015), Grilli et al (2019) and Paris et al (2020), whose models' landslide part governed by Coulomb friction is originated from Savage and Hutter (1989). Grilli et al (2019) and Paris et al (2020) applied this type of model to the case of Krakatau in 2018, demonstrating mass and tsunami behavior well.…”
Section: Numerical Model Of Landslide Mass and Tsunamimentioning
confidence: 99%
See 2 more Smart Citations